Albumin and pre‐albumin levels do not reflect the nutritional status of female adolescents with restrictive eating disorders. (19th January 2016) - Huysentruyt, Koen; De Schepper, Jean; Vanbesien, Jesse; Vandenplas, Yvan
Abstract: Aim: Albumin and pre‐albumin are frequently used as nutritional markers in clinical practice. We examined whether serum albumin and pre‐albumin were predicted by body mass index (BMI), hydration and/or inflammation in female adolescents with a recently diagnosed restrictive eating disorder (RED). Methods: This was a retrospective study of female adolescents with RED from 2002 to 2011. Low albumin and pre‐albumin levels were defined as <3.5 g/dL and <20 mg/dL, respectively. We assessed inflammation using the erythrocyte sedimentation rate (ESR) and dehydration using the haematocrit levels. Results: We included 75 females with a mean age of 15.2 years and 64% had a BMI Z score of <−2. The mean albumin and pre‐albumin levels were 4.8 g/dL and 22.2 mg/dL, respectively, with 24% of the children having low pre‐albumin and none having low albumin levels. The stepwise multiple regression for albumin identified ESR and haematocrit as significant predictors, which explained 14.8% of the variance. Age was the only significant predictor for pre‐albumin, which explained 15.3% of the variance. Conclusion: Albumin, but not pre‐albumin, levels were primarily predicted by low‐grade inflammation and hydration, but not by BMI. These markers should not be used to assess nutritional status in adolescents with RED.